On dirty words: An attempt to intimate the conundrum of the sin - Basthomi, Yazid (citeus, 2010)
This article analyzes the use of dirty words with reference to sociolinguis- tic and Saussurean conceptual frameworks. It starts with a personal-anecdotal ac- count on the difficulties in dealing with didactic issues in relation to the use of dirty words. In the guise of tackling the problem, sociolinguistic explanation is pursued, which, in the end, shows that sociolinguistic explanation is not really adequate to handle the issue. This relates to the possible notion that dirty words might be enacted as a (very) personal expression, devoid of any physical addressees. Saussu- rean linguistic concepts are also explored, and, yet, similar to the sociolinguistic ex- planation, also lacks explanatory rigor in that the Saussurean materiality approach affirms that dirty words are neutral in their very materiality. A hypothetical proposi- tion to deal with dirty words will conclude the article.